2017
DOI: 10.1016/j.apenergy.2017.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Power generation based on the Ca(OH)2/ CaO thermochemical storage system – Experimental investigation of discharge operation modes in lab scale and corresponding conceptual process design

Abstract: Thermochemical storage systems offer in theory promising advantages for a wide range of applications. In particular the reversible reaction of calcium hydroxide to calcium oxide and water vapour is intensively discussed as an alternative storage solution for concentrated solar power plants. The material is cheap, environmentally friendly and discharge temperatures of the reaction of 600 °C and above fit to the operating range of today´s power plants. However, experimental data on the operation of the system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 36 publications
2
31
1
Order By: Relevance
“…However, a lower hydration pressure tended to increase the difference; the difference in the temperatures in the cases of 38.6, 25.0, and 15.8 kPa were 5.2, 7.2, and 21°C, respectively. This tendency is in agreement with the temperatures reported by Schaube et al and Schmidt et al, who used particle or powder beds, the results of which are shown in Figure . To understand the maximum temperature during hydration in laboratory‐scale reactors, further studies have to be conducted at less than 10 kPa.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…However, a lower hydration pressure tended to increase the difference; the difference in the temperatures in the cases of 38.6, 25.0, and 15.8 kPa were 5.2, 7.2, and 21°C, respectively. This tendency is in agreement with the temperatures reported by Schaube et al and Schmidt et al, who used particle or powder beds, the results of which are shown in Figure . To understand the maximum temperature during hydration in laboratory‐scale reactors, further studies have to be conducted at less than 10 kPa.…”
Section: Resultssupporting
confidence: 89%
“…31 Metal oxide/water systems are good candidate for TCES, and it is quite difficult to measure vapor movement in a laboratory scale experimental system because the condensation of water vapor makes flow measurement of water vapor difficult. The unique point of this study is that global conversion of the packed bed was measured through mass-change directly with high precision of 0.1 g with temperature F I G U R E 1 Chemical equilibrium lines of the reaction: [8][9][10] ; conditions of the reaction in laboratory-scale reactors [33][34][35][36] measurements. The experimental data of temperatures and conversion can be used easily for validation of a numerical model for the simplicity of the reactor with high accuracy.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical storage reactors have two main requirements: a fast response during the heat storage/output process and the durability for repetitive operations. In terms of the CaO/Ca(OH) 2 /H 2 O reaction system, previous studies using laboratory‐scale fixed bed reactors have reported several problems that need to be solved to meet these requirements: a low thermal conductivity of the powder bed, formation of centimeter‐scale agglomerates inside the reactors, and change in the bulk volume during repetitive reactions . Therefore, the need to develop suitable materials for a CaO/Ca(OH) 2 /H 2 O reaction system remains.…”
Section: Introductionmentioning
confidence: 99%
“…A complementary development of materials coupled with the optimization of the reactor design would facilitate the enhancement of heat transfer through a storage reactor. Linder et al and Schmidt et al studied fixed bed reactors with embedded heat exchanger plates.…”
Section: Introductionmentioning
confidence: 99%